Forensic Apocalyptic Theology : Karl Barth and the Doctrine of Justification. - Smythe, Shannon Nicole (Emerging scholars., 2016)
Forensic Apocalyptic Theology examines the mature work of Karl Barth in relationship to the question of Paul and the Protestant doctrine of justification. Shannon Nicole Smythe argues that the basis of Barth's revised doctrine of justification is located in his mature Christology, which is both deeply apocalyptic and thoroughly forensic. Smythe discovers in Barth what she terms a "forensic-apocalyptic" approach, which allows him to formulate a doctrine of justification with stronger ties not only to the Reformation doctrine but also to Pauline apocalyptic